Exploring facilitators of transition and adoption to agile methods: a grounded theory study - Gandomani, Taghi Javdani; Zulzalil, Hazura; Abdul Ghani, Abdul Azim; Md. Sultan, Abu Bakar; Sharif, Khaironi Yatim (Academy Publisher, 2014)
Nowadays, changing development approach from traditional to Agile methods has been considered as a strategic decision for achieving Agile values by most software companies and organizations. Due to its nature, moving to Agile software development and adapting to Agile methods need a long time and enough effort. Thus, organizations are faced with a lot of challenges during the transition and adoption process. Providing facilitators can make transition process easier and faster. Conducting a Grounded Theory study on Agile transformation process, involving 33 Agile experts across 13 different countries showed that Agile transition and adoption needs to be supported by several facilitators. Thus, the main contribution of this article is providing eight major facilitators that should be used by Agile teams to support Agile transition and adoption. Some of these facilitators support team members in doing their jobs and empower them against challenges. Some others help them in dealing with challenges or prevent potential problems before occurrence in Agile transition process. Furthermore, some of these facilitators have positive effects on people and motivate them to adapt with their new behaviors. Agile transition and Adoption will be faster and easier if the more facilitators get involve.